2013
DOI: 10.1055/s-0033-1350298
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted MR Imaging of Benign and Malignant Breast Lesions Before and After Contrast Enhancement

Abstract: Mamma 130Janka R et al. 50, 400 und 800) wurde vor und nach KM-Gabe gemessen und die entsprechenden ADC-Werte der Läsionen verglichen. Vor der Berechnung der ADC-Werte wurden die Läsionen bezüglich ihrer konstanten Lokalisation in den diffusionsgewichteten Sequenzen analysiert. Ergebnisse: Die mittlere Größe der Läsionen war 1,5 ± 0,8 cm. Auf der Basis der b50-und b400-Messung betrug der durchschnittliche ADC-Wert der benignen Läsionen 1,89 ± 0,30 × 10 -3 mm 2 /s vor und 1,85 ± 0,28 × 10 -3 mm 2 /s nach KM-Gab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 26 publications
2
27
1
2
Order By: Relevance
“…The twenty false positive cases among lesions with an ADC value of less than 1.44 × 10 -3 mm 2 /s occurred in our series could be explained by the presence of benign nodules with a predominant fibrous component or other benign conditions characterized by inflammatory changes, such as complicated cysts showing low ADC values, probably due to high cellularity, fibrosis, leukocytes, chronic inflammatory elements, as already reported in other series [17,20,25]. On the other side, the two false negative cases among lesions with ADC values of more than 1.44 × 10 -3 mm 2 /s occurred in our series are probably due to the presence of low cellularity breast tumors, such as mucinous forms [22,30].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The twenty false positive cases among lesions with an ADC value of less than 1.44 × 10 -3 mm 2 /s occurred in our series could be explained by the presence of benign nodules with a predominant fibrous component or other benign conditions characterized by inflammatory changes, such as complicated cysts showing low ADC values, probably due to high cellularity, fibrosis, leukocytes, chronic inflammatory elements, as already reported in other series [17,20,25]. On the other side, the two false negative cases among lesions with ADC values of more than 1.44 × 10 -3 mm 2 /s occurred in our series are probably due to the presence of low cellularity breast tumors, such as mucinous forms [22,30].…”
Section: Discussionsupporting
confidence: 84%
“…Also in the case of breast lesions, the mean ADC values decreased after CMI in benign and malignant lesions probably due to the decrease of micro-perfusion induced by contrast material, especially in hyper-vascular lesions such as malignant tumors [22]. In fact, ADC values depend not only on Brownian motion of molecules but also on capillary blood circulation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In patients with known breast cancer and clinically suspicious findings, DW imaging has been shown to be of high value in discriminating malignant from benign lesions (8,(16)(17)(18)(19)(20)(21). It has been suggested that DWIBS displays breast lesions even better than DW imaging (9,10), because the background suppression makes breast lesions more conspicuous.…”
Section: Adc Maps and Correlation With Histopathologic Gradesmentioning
confidence: 99%